1989
DOI: 10.1111/j.1365-2265.1989.tb01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Acth and Cortisol Responses to Provocative Testing With Glucagon and Insulin Hypoglycaemia in Normal Subjects

Abstract: The glucagon stimulation test (GST) is often used to assess pituitary ACTH reserve, particularly when other tests are contra-indicated. In a preliminary investigation, in patients with pituitary disease, we failed to demonstrate the ACTH dependence of the cortisol response. We have therefore compared the ACTH, cortisol and glucose responses to glucagon (1 mg s.c.), insulin (0.2 U/kg i.v., ITT) and placebo in six healthy male volunteers, sampling every 10 min for 6 h. During the GST, mean +/- SD serum cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 12 publications
7
41
1
1
Order By: Relevance
“…Additionally, no correlation between BMI and age to peak GH responses were observed, peak GH responses occurred mainly between 120 and 180 minutes consistent with previous studies, 27,30 and that, overall, the GST was a well tolerated test. Nevertheless, these 21,22,28 and previous studies 20,23,24,31 did not specifically evaluate patients with glucose intolerance and frank diabetes and, for this reason, the characteristic of the GST and its reliability in testing for GHD in this population remains unclear.…”
Section: Historical Perspective Of the Use Of Glucagon Stimulation Tesupporting
confidence: 74%
“…Additionally, no correlation between BMI and age to peak GH responses were observed, peak GH responses occurred mainly between 120 and 180 minutes consistent with previous studies, 27,30 and that, overall, the GST was a well tolerated test. Nevertheless, these 21,22,28 and previous studies 20,23,24,31 did not specifically evaluate patients with glucose intolerance and frank diabetes and, for this reason, the characteristic of the GST and its reliability in testing for GHD in this population remains unclear.…”
Section: Historical Perspective Of the Use Of Glucagon Stimulation Tesupporting
confidence: 74%
“…The response to GHRH/arginine was stratified by BMI (cut-off for severe GHD: GH!11.5 mg/l for BMI !25 kg/m 2 , !8 mg/l for BMI 25-30 kg/m 2 and !4.2 mg/l for BMI O30 kg/m 2 ) (17). Cortisol insufficiency was defined as a peak cortisol !500 nmol/l to both glucagon and synacthen testing (18). Gonadotrophin deficiency in males was defined as an early morning testosterone of !8.5 nmol/l (lower limit of normal range for assay) on two occasions with gonadotrophins within the normal range, and confirmation testing at 12 months also required a free testosterone concentration below the normal range in addition to the above.…”
Section: Definition Of Biochemical Hormone Deficienciesmentioning
confidence: 99%
“…High glucagon concentrations may also contribute to the marked increase in plasma ACTH levels found in adrenalectomized and autotransplanted rats (Table 1), since previous studies demonstrated that administration of glucagon evokes a considerably rise in the blood levels of ACTH [24,25]. It has also been reported that systemic or intracerebroventricular administration of glucagon raises plasma concentration of corticosterone in rats [26] and cortisol in humans [27,28]. Thus, it may well be that increased glucagon levels contribute to the partial recovery of plasma corticosterone observed in autotransplanted animals (Fig.…”
Section: Discussionmentioning
confidence: 95%